Fuel poverty, excess winter deaths, and energy costs in Vermont: Burdensome for whom?. (March 2016) - Teller-Elsberg, Jonathan; Sovacool, Benjamin; Smith, Taylor; Laine, Emily
Abstract: Energy, whether from electricity, natural gas, heating oil, propane, kerosene, or wood, is essential for the well-being of many Americans, yet those who spend more than 10 percent of their income of energy services can be considered "fuel poor." This study assesses the extent and severity of fuel poverty in Vermont. It analyzes energy burdens in Vermont by household income deciles, using data from the Census Bureau's American Community Survey. Approximately 71, 000 people suffered from fuel poverty in Vermont in 2000, and in 2012 the number rose to 125, 000, or one in five Vermonters. Startlingly, fuel poverty grew 76 percent during this period. Excess winter deaths, caused potentially by fuel poverty, kill more Vermonters each year than car crashes. The article then provides 12 policy recommendations based on a small sample of elite semi-structured research interviews. These include suggestions that the Vermont legislature better fund investments in weatherization among low-income households; that community groups and social service agencies scale up the training of energy efficiency coaches; that state agencies endorse improvements in housing efficiency and appropriate fuel switching; and that utilities and fuel providers offer extra assistance for disconnected households and allow for on-bill financing of efficiency improvements. Highlights: Those spending 10 percent of their monthly income or more on energy services are in "fuel poverty". In this study we analyze the energy burden in Vermont by household income deciles. We calculate that excess winter deaths caused potentially by fuel poverty kill more Vermonters each year than car crashes. We conclude with implications for energy planners and policymakers.